Single-Bud Expression Analysis of Bud Dormancy Factors in Peach - Ana Puertes; Helin Polat; Luis Andrés Ramón-Núñez; Matilde González; Gema Ancillo; Elena Zuriaga; Gabino Ríos (Plants, 2023)
Transcriptomic and gene expression analysis have greatly facilitated the identification and characterization of transcriptional regulatory factors and effectors involved in dormancy progression and other physiological processes orchestrated during bud development in peach and other temperate fruit species. Gene expression measurements are most usually based on average values from several or many individual buds. We have performed single-bud gene analysis in flower buds of peach across dormancy release using amplicons from the master regulatory DORMANCY-ASSOCIATED MADS-BOX (DAM) factors, several jasmonic acid biosynthetic genes, other genes related to flowering development, cell growth resumption, and abiotic stress tolerance. This analysis provides a close view on gene-specific, single-bud variability throughout the developmental shift from dormant to dormancy-released stages, contributing to the characterization of putative co-expression modules and other regulatory aspects in this particular tissue.